Hubungan Ekspresi Protein Bcl-2 Jaringan dengan Disease Free Survival 2 Tahun Pasien Kanker Epitel Ovarium di Rumah Sakit Dr. Soetomo, Surabaya - ARDHANU KUSUMANTO (Indonesian Journal of Cancer, 2015)
Ovarian cancer is one of the most common causes of death among gynecological malignancies. Previous reports have shown that the anti-apoptotic protein Bcl-2 is over expressed in many solid neoplasms, including ovarian cancers, and contributes to neoplastic transformation and drug-resistant disease, resulting in poor clinical outcome. This study is an observational descriptive cross-cut design to determine the role of Bcl-2 protein expression as a two year disease free survival prognostic factor in patients with epithelial ovarian cancer. Data were extracted from 37 patients treated with primary surgery with or with out secondary surgery followed by adjuvant therapy, from January 1st2010 to December 31st2011, at the Division of Gynecologic Oncology, Department of Obstetric and Gynecology, Medical Faculty of Airlangga University, Surabaya, Indonesia, were retrospectively analyzed. Bcl-2 expression were analized by immunohistochemistry study. The reccurency evaluation was done by CT-scan. The time to follow-up was 24 months since patients diagnosis. Spearman and Phi correlation test were used for analysis. In this study, two year disease free survival rate of patients was found 78.4% (29 of 37), respectively, and Spearman and Phi correlation test showed that there were no significant relation between Bcl-2 expression and ovarian cancer recurrence (p=0.084). Expression of Bcl-2 as an anti-apoptotic protein in ovarian cancer was not significantly related with the tumor reccurency as a marker of the two year disease free survival.